2009
DOI: 10.1002/ps.1850
|View full text |Cite
|
Sign up to set email alerts
|

Bromadiolone susceptibility in wild and laboratory Mus musculus L.(house mice) in Buenos Aires, Argentina

Abstract: We found evidence of the presence of anticoagulant resistant M. musculus L. in the study area. Feeding behaviour may have contributed to increasing the time of survival, and may be a mechanism that allows metabolic clearance of the bromadiolone. Under field conditions control with anticoagulants would be less effective because animals have alternative food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…However, the different consumption strategies of males and females did not seem to have any effect on survival rates under these experimental conditions, since both sexes showed similar survival curves when fed bromadiolone and wheat baits simultaneously. Other authors, who offered only bromadiolone to rodents, did not find any differences in survival times of males and females either (Guidobono et al, 2010). In contrast, in another study, it was found that females were less susceptible than males to the effects of anticoagulants (Ashton et al, 1987).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, the different consumption strategies of males and females did not seem to have any effect on survival rates under these experimental conditions, since both sexes showed similar survival curves when fed bromadiolone and wheat baits simultaneously. Other authors, who offered only bromadiolone to rodents, did not find any differences in survival times of males and females either (Guidobono et al, 2010). In contrast, in another study, it was found that females were less susceptible than males to the effects of anticoagulants (Ashton et al, 1987).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, it may also move from other farms, probably using riparian habitats as corridors (León et al, , 2013. More recently, a study on bromadiolone resistance reported that 8% of M. musculus from these farms were resistant (Guidobono et al, 2010).…”
Section: Consumption Pattern Of Bromadiolone In Presence Of Alternatimentioning
confidence: 99%
See 3 more Smart Citations